2006
DOI: 10.1074/jbc.m605473200
|View full text |Cite
|
Sign up to set email alerts
|

A Carboxyl-terminal Hydrophobic Interface Is Critical to Sodium Channel Function

Abstract: Perturbation of sodium channel inactivation, a finely tuned process that critically regulates the flow of sodium ions into excitable cells, is a common functional consequence of inherited mutations associated with epilepsy, skeletal muscle disease, autism, and cardiac arrhythmias. Understanding the structural basis of inactivation is key to understanding these disorders. Here we identify a novel role for a structural motif in the COOH terminus of the heart Na V 1.5 sodium channel in determining channel inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…We have shown that molecular interactions taking place in the C-terminal cytoplasmic domain of Na ϩ channel ␣ subunit, where M1841T is located, can effectively rescue the mutant channel. This domain is functionally important, because it modulates inactivation properties and contains several binding sites for modulatory proteins (Mantegazza et al, 2001;Abriel and Kass, 2005;Glaaser et al, 2006). M1841T lies in an area that includes a ␤1/␤3 binding site (Spampanato et al, 2004), and we have shown that the interaction between the C-terminal domains of ␣ and mutant ␤1-C121W subunits is sufficient to induce ϳ60% of the rescue observed with wild-type ␤1.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that molecular interactions taking place in the C-terminal cytoplasmic domain of Na ϩ channel ␣ subunit, where M1841T is located, can effectively rescue the mutant channel. This domain is functionally important, because it modulates inactivation properties and contains several binding sites for modulatory proteins (Mantegazza et al, 2001;Abriel and Kass, 2005;Glaaser et al, 2006). M1841T lies in an area that includes a ␤1/␤3 binding site (Spampanato et al, 2004), and we have shown that the interaction between the C-terminal domains of ␣ and mutant ␤1-C121W subunits is sufficient to induce ϳ60% of the rescue observed with wild-type ␤1.…”
Section: Discussionmentioning
confidence: 99%
“…2C). Mutations of hydrophobic residues in Na V 1.5 have also been shown to lead to perturbation of channel function (49). Such mutations would be expected to significantly destabilize the domain and may perturb its structure leading to alteration of channel function.…”
Section: Discussionmentioning
confidence: 99%
“…However, this position is within the predicted fifth helix and thus not the region involved in formation of the EF-hand motifs (44 -47, 50 -53). Therefore, alterations at this position are unlikely to directly disrupt the overall secondary structure of the pair of EF-hands that are formed by intermolecular interactions between side chains in the interface of helices I with IV and II with III (44,49,54). Furthermore, the Na v 1.3 K1826E and Na v 1.2 E1880K mutations are unlikely to function as helix breakers because the replacement amino acids have higher helical propensities than the original amino acids (55).…”
Section: Discussionmentioning
confidence: 99%